Reconciling the Historian's Craft and Religious Belief: A Forum. (Fides et historia, 2011)
An introduction is presented to a special section featuring comments from a session of the American Historical Association's (AHA's) 2009 annual meeting titled "Reconciling the Historian's Craft with Religious Belief".